Hypermodule Deep Learning Inquiry–Steam: A Theoretical Framework And Science Teachers’ Perceptions In The Digital Era - Wahyu Sugiarto; Sabar Nurrohman; Antuni Wiyarsi; Laifa Rahmawati (Jurnal Pendidikan Sains Universitas Muhammadiyah Semarang, 2026)
Low scientific literacy and limited collaborative learning practices remain persistent challenges in science education, particularly in digitally constrained contexts where technology integration is uneven. This study develops a theoretical framework of the Hypermodule Deep Learning Inquiry–STEAM by integrating deep learning pedagogy, inquiry-based learning, and STEAM education into a unified digital learning model, while examining science teachers' perceptions of its implementation. A qualitative, exploratory survey design involved 38 junior high school science teachers in Biak Numfor Regency, Papua, Indonesia. Data were collected through open-ended questionnaires and semi-structured interviews, and were analysed thematically using open, axial, and selective coding. Findings reveal that teachers perceive deep learning as meaningful and transferable learning, inquiry as fostering scientific reasoning, and STEAM as promoting creativity and collaboration; however, these approaches remain fragmented in classroom practice. The study contributes a conceptual hypermodule framework linking pedagogical constructs, digital learning features, and targeted outcomes related to scientific literacy and collaboration skills. Future research should empirically test the framework’s effectiveness across diverse educational contexts and examine its impact on student learning outcomes through mixed-method or experimental designs.